New developments in inhaler devices within pharmaceutical companies: A systematic review of the impact on clinical outcomes and patient preferences. Issue 11 (November 2015) - Ninane, Vincent; Vandevoorde, Jan; Cataldo, Didier; Derom, Eric; Liistro, Giuseppe; Munghen, Evert; Peché, Rudi; Schlesser, Marc; Verleden, Geert; Vincken, Walter
Abstract: Background: Pharmaceutical companies offer an increasing number of inhaler devices, whether or not together with new substances, for maintenance treatment of patients with COPD or asthma. However, well-designed studies to support these developments are scarce. Objectives: The aim of this research was to evaluate how far new developments of inhaler devices are scientifically supported and translate into improvements of patient preferences and/or clinical outcomes. Methods: A systematic literature review was performed to retrieve randomised controlled trials in patients with COPD or asthma that studied the in-company evolution of inhaler devices. Results were tabulated and discussed. Results: A total of 30 studies were found comparing Respimat ® vs. HandiHaler ®, Diskus ® (Accuhaler ® ) vs. Diskhaler ® (Rotadisk ® ) or pMDI, Ellipta ® vs. Diskus ® (Accuhaler ® ), Nexthaler ® vs. pMDI, or Breezhaler ® vs. Aerolizer ® . These studies show that developments of inhaler devices may improve patient satisfaction but do not lead to demonstrable improvements in clinical efficacy. Current changes of devices are most commonly parallelled by changes in administration frequency towards once daily treatment. The only well-documented effect was found for the Respimat ® Soft Mist™ Inhaler, which realises a more than 3-fold lowering of the once-daily tiotropium dose through increased performance of the inhaler device. There are however, no data on clinical efficacy or safety comparing the two devices at the same dosage. Conclusions: Future developments of inhaler devices should all require well-designed studies to demonstrate patient benefit.